2018
DOI: 10.3390/v10070388
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection Patterns in Individual Ixodes scapularis Ticks Reveal Associations between Viral, Eukaryotic and Bacterial Microorganisms

Abstract: Ixodes scapularis ticks harbor a variety of microorganisms, including eukaryotes, bacteria and viruses. Some of these can be transmitted to and cause disease in humans and other vertebrates. Others are not pathogenic, but may impact the ability of the tick to harbor and transmit pathogens. A growing number of studies have examined the influence of bacteria on tick vector competence but the influence of the tick virome remains less clear, despite a surge in the discovery of tick-associated viruses. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 78 publications
2
57
2
Order By: Relevance
“…However, we have excluded common environmental microbes demonstrated to be artifacts from contaminated reagents, such as Delftia, Comamonas, Acidovorax, and others (Salter et al, 2014). Sequence-based studies indicate a larger variety of bacterial residents may temporarily survive in this tick species (Benson et al, 2004;Narasimhan et al, 2014;Rynkiewicz et al, 2015;Van Treuren et al, 2015;Zolnik et al, 2016Zolnik et al, , 2018Abraham et al, 2017;Cross et al, 2018;Landesman et al, 2019;Tokarz et al, 2019), but other reports suggest that many of the detectable bacteria from such studies may have been of environmental origin or introduced from contaminated reagents (Martin and Schmidtmann, 1998;Salter et al, 2014;Ross et al, 2018;Zolnik et al, 2018).…”
Section: Microbiota Of I Scapularismentioning
confidence: 99%
See 3 more Smart Citations
“…However, we have excluded common environmental microbes demonstrated to be artifacts from contaminated reagents, such as Delftia, Comamonas, Acidovorax, and others (Salter et al, 2014). Sequence-based studies indicate a larger variety of bacterial residents may temporarily survive in this tick species (Benson et al, 2004;Narasimhan et al, 2014;Rynkiewicz et al, 2015;Van Treuren et al, 2015;Zolnik et al, 2016Zolnik et al, , 2018Abraham et al, 2017;Cross et al, 2018;Landesman et al, 2019;Tokarz et al, 2019), but other reports suggest that many of the detectable bacteria from such studies may have been of environmental origin or introduced from contaminated reagents (Martin and Schmidtmann, 1998;Salter et al, 2014;Ross et al, 2018;Zolnik et al, 2018).…”
Section: Microbiota Of I Scapularismentioning
confidence: 99%
“…Anaplasma phagocytophilum i, p 1.9-18% (N, A) Adelson et al, 2004;Aliota et al, 2014;Cross et al, 2018;Tokarz et al, 2019 Bartonella spp. p 13-90% (L, N) Adelson et al, 2004;Rynkiewicz et al, 2015 Ehrlichia spp.…”
Section: Microbiota Of I Scapularismentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, 12S rRNA gene sequences homologous to sequences from larial nematodes were detected in I. scapularis ticks in Connecticut [3]. Subsequent metagenomic analyses of I. scapularis from Wisconsin and our study from New York and Connecticut also reported Filarioidea sequences [4,5]. Because larial nematodes are implicated in veterinary and human disease and there is a high degree of human contact with I. scapularis, we sought to genetically characterize this nematode (tentatively named Ixodes scapularis-associated nematode, or ISN) and determine the level of human exposure.…”
Section: Introductionmentioning
confidence: 51%